A novel battery thermal management system coupling with PCM and optimized controllable liquid cooling for different ambient temperatures. (15th January 2020) - Kong, Depeng; Peng, Rongqi; Ping, Ping; Du, Jin; Chen, Guoming; Wen, Jennifer
Highlights: A novel Coupled PCM-liquid cooling system (CPLS) for Li-ion battery pack. Design of CPLS is optimized for the thermal performance of battery pack. Effectiveness of CPLS is verified by the designed experiments. Controlling strategy for the velocity and inlet temperature of coolant. Improved cooling performance and energy-saving at different ambient temperatures. Abstract: In order to improve the working performance of the lithium-ion battery pack in continuous operation under different ambient temperatures, a coupled composite phase change material and liquid cooling thermal management system is proposed. The simulation for this system under a cycle that a 3C rate discharging and then a 0.5C charging was conducted, as well as comparison tests concerning factors such as cell-to-cell spacing, cell-to-tube distance, channel number and coolant velocity. Simulation results showed that the coupled system with suitable design exhibited good thermal performance at an ambient temperature of 30 °C, which kept the maximum surface temperature and the temperature difference of the battery pack at 41.1 °C and 4 °C at the end of 3C discharge. Then, the latent heat of phase change material was also recovered by the liquid cooling during the 0.5C charge. Specially designed experiments have also been conducted to verify the effectiveness and practicability of the proposed coupled system. Based on this system, a liquid cooling strategy was proposed for controlling the velocity and inlet temperature of coolant by monitoring the temperature of the phase change material and environment. This further improved the thermal performance of the battery pack during cycling at different ambient temperatures and significantly reduced the unnecessary power consumption of liquid cooling during this process.